Thermal, structural and mechanical characterization of Nephila clavipes spider silk in southwest Colombia (2020)
Some physical properties of spider silks, including mechanical strength and toughness, have been studied in many laboratories worldwide. Given that this silk is organic in nature, composed of protein, and has similar properties to metal wires or polymers, it has the potential for application in medicine, nanoelectronics, and other related areas. In this study, we worked on spider silk from the Nephila clavipes species collected from the wild and kept it in the nursery of the Autonomous University of the West, Cali, Colombia, to determine its physical, thermal, and mechanical properties, seeking possible applications in the medical and industrial sectors and comparing the material properties of the silk from the species from southwestern Colombia with those of the previously studied species from other regions. The mechanical characterization of the material was performed using a universal testing machine; thermal behavior was captured by a thermogravimetric analysis, differential scanning calorimetry, and mass spectrometry; and structural characterization was performed using diffraction X-rays. The results of the thermal characterization demonstrate that the spider silk loses 10 % of water content at 150 °C with significant changes at 400 °C, while the mechanical characterization indicates that the spider silk is much tougher than Kevlar 49 and Nylon 6 since it is capable of absorbing more energy before rupture